PERAN MOTIVASI KERJA DALAM MEMEDIASI PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA FASKEL (Studi Kasus Fasilitator Kelurahan pada Program Kota Tanpa Kumuh Sulawesi Tenggara) - Sitti Halmianti; Endro Sukotjo; Muhammad Masri; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to explain and examine the effect of leadership style on employee performance (Faskel), work discipline on employee performance (Faskel), and work motivation on performance (Faskel), also to examine and explain the role of work motivation in mediating the influence of leadership style, work discipline on employee performance (Faskel). This research approach is survey with explanatory research design. Data collection was carried out in a cross-sectional manner using an instrument in the form of a questionnaire. The population in this study were all 53 staff of KOTAKU Program in Southeast Sulawesi. The sampling technique is a saturated sample (census) where the entire population is used as the research sample. The data analysis technique to answer the research hypothesis is Partial Least Square (PLS).The results showed that leadership style had a significant effect on work motivation and employee performance (Faskel), work discipline had a significant effect on motivation and employee performance (Faskel). Then work motivation has a significant effect on employee performance (Faskel). In addition, the results of this study indicate that work motivation acts as a partial mediation of the influence of leadership style on employee performance (Faskel). The conclusion of this study shows that a good leadership style can increase the motivation and employee performance (Faskel), then good work discipline can increase the motivation and employee performance (Faskel). Furthermore, high work motivation can improve the employee performance of (Faskel). In addition, work motivation acts as partial mediation between the influence of leadership style on employee performance (Faskel), then work motivation also acts as partial mediation between the influence of work discipline on employee performance (Faskel). Keywords: Leadership Style, Work Discipline, Work Motivation, and Employee Performance (FASKEL).